Palmoplantar pustulosis and smoking. Issue 6499 (28th September 1985) - O'Doherty, C J; MacIntyre, C
Abstract : A multicentre case-control study of 216 patients with palmoplantar pustulosis and 626 controls with miscellaneous dermatoses showed a considerably higher prevalence of smoking in the group with palmoplantar pustulosis. This was the first indication that smoking may be an important factor in this skin disease, possibly by affecting the inflammatory responses of the skin.